2017
DOI: 10.3857/roj.2017.00367
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic extended-field irradiation with concurrent chemotherapy for pelvic lymph node-positive cervical cancer

Abstract: PurposeThis study aimed to evaluate whether prophylactic extended-field pelvic radiotherapy (EF-PRT) yields better results than standard whole pelvic radiotherapy (WPRT) in patients with pelvic lymph node-positive cervical cancer treated with concurrent chemoradiotherapy (CCRT).Materials and MethodsA total of 126 cases of stage IB-IVA cervical cancer that had pelvic lymph node involvement in magnetic resonance imaging and were treated with CCRT between 2000 and 2016 were reviewed. None of the patients had para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…No survival differences were observed between the 2 groups. 13 In the study by Oh et al, 14 74 patients with cervical cancer were treated with pelvic RT and 52 patients underwent extended-field RT. The 10-year DFS, OS, and cumulative PALNF rates were not significantly different between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No survival differences were observed between the 2 groups. 13 In the study by Oh et al, 14 74 patients with cervical cancer were treated with pelvic RT and 52 patients underwent extended-field RT. The 10-year DFS, OS, and cumulative PALNF rates were not significantly different between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The 10-year DFS, OS, and cumulative PALNF rates were not significantly different between the 2 groups. 14 A study from Canada conducted multivariate analysis for 228 patients with cervical cancer and found that extended-field RT was not significantly associated with DFS, OS, and para-aortic relapse. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, OS and DFS were not significantly different between the two groups ( 34 ). In retrospective studies conducted by Yi et al ( 35 ), Oh et al ( 36 ), Park et al ( 37 ), and Yap et al ( 38 ), patients with cervical cancer did not benefit from prophylactic EFI. In the study by Park et al ( 37 ), 203 patients with LACC were included.…”
Section: Prophylactic Efi Combined With Concurrent Chemotherapymentioning
confidence: 90%
“…The eligibility criteria differ between studies on prophylactic EFI, and the criteria include cervical cancer ( 33 , 35 ), LACC ( 37 , 40 ), FIGO stage IB-IVA ( 34 ), FIGO stage IIB-IVA ( 32 ), and pelvic LN involvement ( 36 , 40 , 47 ), among others. This is an important reason why these studies have contradictory results.…”
Section: The Indications Of Prophylactic Efimentioning
confidence: 99%